The Incidence of an Extended Ace Corporation Tax - Ernst Fehr; Wolfgang Wiegard (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper deals with the efficiency and distributional consequences of a switch from the current German income and corporate tax system to one special variant of an intertemporally neutral tax, an extended ACE (allowance for corporate equity) corporation tax. This tax is favoured by the IFS Capital Taxes Group and was implemented in Croatia in 1994. We not only calculate the welfare consequences of introducing the ACE, but also separate the efficiency effects from intragenerational as well as intergenerational redistribution. The quantitative analysis is based on a dynamic simulation model of the Auerbach-Kotlikoff type which distinguishes between five income classes within each generation. The numerical results indicate that such a fundamental tax reform could yield enormous efficiency gains without necessarily increasing income inequality.
Keywords: 330; Corporate taxation; intra- and intergenerational incidence; dynamic CGE modeling